Simultaneous Seroprevalence to Toxoplasma gondii, Cytomegalovirus and Rubella Virus in Childbearing Women from Western Romania - Mocanu, Adelina Geanina; Gorun, Florin; Ciohat, Ioana; Navolan, Dan; Malita, Daniel; Vilibic-Cavlek, Tatjana; Dahma, George; Neamtu, Radu; Popescu, Daniela; Cioca, Andreea; Craina, Marius (Medicina (Kaunas, Lithuania), 2021)
Background and Objectives: Toxoplasma gondii, cytomegalovirus (CMV) and rubella virus, besides other agents, belong to a group named the TORCH complex. Research on the epidemiology of these agents in women is of particular interest, as primary infection during pregnancy could cause severe damage to the fetus. Women who had contracted infection before pregnancy develop IgG antibodies, so the fetus is protected in case of contact with the same agent. Our scope was to identify the childbearing women simultaneously protected or susceptible to a primary infection to two or three agents mentioned above. Materials and Methods: A cross-sectional study was performed on 6961 fertile Caucasian women from Western Romania, to analyze the simultaneous seroprevalence to two or three of the pathogens from the TORCH complex: Toxoplasma gondii, CMV, and rubella virus. Sampling was conducted at two time points: 2008–2010 (group 1; 1461 participants) and 2015–2018 (group 2; 5500 participants). Results: The percentage of women simultaneously seropositive to IgG-anti-Toxoplasma gondii/IgG-anti-CMV, IgG-anti-Toxoplasma gondii/IgG-anti-rubella, IgG-anti-CMV/IgG-anti-rubella or IgG-anti-Toxoplasma gondii and IgG-anti-CMV/IgG-anti-rubella antibodies decreased between the two groups (2008–2010 vs. 2015–2018): 41.4% vs. 36.1%, OR = 0.79, p = 0.0002; 41.8% vs. 35.7%, OR = 0.77, p < 0.0001; 88.9% vs. 83.6%, OR = 0.63, p < 0.0001; 39.6% vs. 33.2%, OR = 0.75, p < 0.0001. When comparing women from urban and rural areas, the simultaneous seroprevalence was higher in rural areas. In women tested 2008–2010 (group 1) the simultaneous seroprevalence (urban vs. rural) was: 38.4% vs. 49.1%, OR = 1.54, p = 0.0002; 38.4% vs. 50.6%, OR = 1.64, p < 0.0001; 88.8% vs. 89.2%, OR = 1.04, NS; 36.4% vs. 47.7%, OR = 1.58, p = 0.0001. A similar trend was found in women tested in group 2. Conclusions: The rate of simultaneous seropositivity to Toxoplasma gondii, CMV and rubella virus among Romanian women of reproductive age decreased significantly between 2008–2010 and 2015–2018 and the susceptibility to infections increased. It is necessary to apply increased prevention measures among susceptible pregnant women.